Efektivitas Pemberian ASI Eksklusif dengan Kejadian Stunting pada Balita di PMB Umay Bekasi - Umay Umay; Masluroh Masluroh (Malahayati Nursing Journal, 2024)
ABSTRACT Based on the Indonesian Nutrition Status Survey (SSGI) of the Ministry of Health, the prevalence of stunting in children under five in Indonesia will reach 21.6% in 2022. (Ministry of Health, 2023) Based on the prevalence of stunting, the incidence of stunting in Indonesia is still a problem because the national prevalence is still above the tolerance set by the WHO, which is only 20%. Knowing the effectiveness of exclusive breastfeeding with the incidence of stunting in toddlers at PMB Umay Bekasi in 2023. In a cross-sectional research design, the sample in this study amounted to 57 respondents. The sample technique used total sampling. Analysis was carried out using univariate and bivariate methods using chi square. Most of the respondents at PMB Umay Bekasi in 2023 did not experience stunting, namely 50 (87.7%). There was a relationship between exclusive breastfeeding and the incidence of stunting in toddlers. Midwives are expected to further optimise exclusive breastfeeding counselling for mothers in an effort to prevent stunting in toddlers. Keywords: Stunting, ASI Exclusive  ABSTRAK Berdasarkan Survei Status Gizi Indonesia (SSGI) Kementerian Kesehatan, prevalensi balita stunting di Indonesia mencapai 21,6% pada 2022. (Kemenkes, 2023). Berdasarkan prevalensi stunting tersebut, kejadian stunting di Indonesia masih menjadi masalah karena prevalensi nasional masih diatas toleransi yang ditetapkan WHO yang hanya 20%. Mengetahui efektivitas pemberian ASI Eksklusif dengan kejadian stunting pada balita di PMB Umay Bekasi Tahun 2023. Rancangan penelitian Cross Sectional, sampel dalam penelitian ini berjumlah 57 responden. Tehnik Sampel menggunakan total sampling, Analisis dilakukan secara univariate dan bivariate menggunakan chi square. Sebagian besar responden di di PMB Umay Bekasi tahun 2023 tidak mengalami stunting yaitu sebesar 50 (87,7%), ada Hubungan pemberian ASI Eksklusif dengan kejadian stunting pada Balita. Bidan diharapkan untuk lebih megoptimalkan lagi penyuluhan ASI Eksklusif pada ibu, sebagai salah satu upaya pencegahan stunting pada Balita. Kata Kunci: Stunting, ASI Eksklusif